Treatment of large osteosarcoma in children: new approach - Kobys, V.L.; Konovalenko, V.F.; Repinа, N.V.; Golovko, T.S.; Gulak, L.O.; Tarasova, T.O.; Zaharycheva, E.V.; Matyushok, O.F. (Experimental Oncology, 2013)
Aim - to improve the treatment results of patients with locally advanced osteosarcoma with large volume using neoadjuvant chemotherapy (NACT) (ifosfamide at a dose of 18 g/ml) and planning of organ-conserving surgery by evaluating the state of tumor pseudocapsule. A study group included 46 children aged from 7 to 18 years, mean age - 12 years. In 68 % of the patients tumor volume was larger or significantly larger than 200 ml (from 27 to 2400 ml), mean tumor volume was 342 ml. All patients have been examined by X-ray radiography, CT, Doppler ultrasound. Convenient chemotherapy consisted of methotrexate at a dose of 12 g/ml, cisplatin (120 mg/ml) in combination with doxorubicin (75 mg/ml). If such chemotherapy was considered ineffective with the use of an algorithm for determination of chemotherapy efficacy, 2 cycles of chemotherapy with ifosfamide at a dose of 18 g/ml per course have been applied. At the stage of planning of organ-conserving surgery, the state of tumor pseudocapsule was analyzed. In 6 months post-operative chemotherapy was carried out with the use of methotrexate, cisplatin with doxorubicin, ifosfamide at the same doses. Myelotoxicity of ifosfamide treatment at a dose of 18 g/ml is comparable to that of to a course of doxorubicin + cisplatin: the depth of leucopenia was significantly higher (p << 0,05), the duration of agranulocytosis is similar after such therapies. In the study group, 69,6 % patients have reached grade 3 - 4 pathomorphosis. Organ-conserving surgery was performed in 86,9 % of the patients. Local tumor recurrence was registered in 15,2 % patients of the study group. 5-year relapse-free survival was achieved in 62 +- 10 % (p = 0,02), the overall 5-year survival - 76,5 +- 9 % (p = 0,02). Conclusions: introduction of ifosfamide at a dose of 18 g/ml in the treatment scheme of pediatric patients with locally advanced osteosarcoma along with individualization of pre-oper- g/ml in the treatment scheme of pediatric patients with locally advanced osteosarcoma along with individualization of pre-oper- g/ml in the treatment scheme of pediatric patients with locally advanced osteosarcoma along with individualization of pre-oper- ml in the treatment scheme of pediatric patients with locally advanced osteosarcoma along with individualization of pre-oper- in the treatment scheme of pediatric patients with locally advanced osteosarcoma along with individualization of pre-oper- in the treatment scheme of pediatric patients with locally advanced osteosarcoma along with individualization of pre-oper- in the treatment scheme of pediatric patients with locally advanced osteosarcoma along with individualization of pre-oper- osteosarcoma along with individualization of pre-oper along with individualization of pre-operative chemotherapy, pre-oper ative analysis of NACT efficacy and the state of tumor pseudocapsule during planning stage of organconserving surgery significantly improves efficacy of the therapy in patients with large tumor volume. Key Words: osteosarcoma, children, pseudocapsule tumors, tumor volume, chemotherapy.